Balloon enteroscopy-assisted radial incision and cutting method for refractory hepaticojejunostomy anastomotic strictures - Inoue, Tadahisa; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ohashi, Tomohiko; Nakade, Yukiomi; Sumida, Yoshio; Ito, Kiyoaki; Nakao, Haruhisa; Yoneda, Masashi (Endoscopy, 2019)
Background Balloon enteroscopy-assisted balloon dilation and temporary biliary stent placement are effective for hepaticojejunostomy anastomotic strictures (HJAS), but the re-stenosis rates are relatively high. We examined the feasibility and efficacy of a novel treatment technique for refractory HJAS, called balloon enteroscopy-assisted radial incision and cutting (BE-RIC).Methods Between January 2016 and June 2018, 11 patients with refractory HJAS that recurred after balloon dilation and/or stent placement, underwent BE-RIC. We evaluated the technical success, clinical success, adverse events, and re-stenosis rates associated with BE-RIC. Results The technical success rate of BE-RIC was 91 % (10/11). Clinical success was achieved in all patients who underwent technically successful procedures. The procedure-related adverse event rate was 9 % (1/11). No re-stenosis was observed during the follow-up period; 9 patients were followed up for more than 6 months, and of these, 5, 4, and 2 patients were followed up for more than 12, 18, and 24 months, respectively, without re-stenosis.Conclusions BE-RIC for refractory HJAS showed favorable results. BE-RIC might be a useful option for treating refractory HJAS.